Effect of Tillage on Weed Population and Seed Reserve in Arid Soils - Kumari, Jalaja; Sundaramoorthy, S; Sen, D N (Annals of Arid Zone, 2016)
Experiments were conducted to evaluate the effect of differential tillage practices on weed population in rainy season. Zero tillage has been found to be very effective in controlling Cyperusrofllndus Linn, as the rhizomes do not become free to sprout. Dicots and grasses also showed less presence. However, ploughing the land once or twice and leaving fallow showed insignificant variation in presence of dicots and grasses. The land once prepared and left fallow, and then again ploughed in the same season, resulted in lesser emergence of weeds.